Reflecting on our past: reconciling a divided nation through listening - Ayee, E. S. A. (Koers, 2010)
The miracle of a relatively peaceful transition from apartheid to a non-racial democratic rule in South Africa stunned political pundits and observers. After decades of dehumanising laws which led to unbelievable racial conflict and the killing of many people, the country witnessed the birth of a new dispensation. This article briefly recounts the tragic history of South Africa, the current challenges the country faces for sustainable peaceful coexistence between the various racial groups, and the role that listening played and should continue to play in the process of national reconciliation.